IMPLEMENTASI MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) MELALUI KEGIATAN LESSON STUDY PADA MATA KULIAH BIOLOGI UMUM DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS SRIWIJAYA - ., Rahmi Susanti (SEMIRATA 2015, 2015)
Lesson study at Biology Education Study Program of FKIP Sriwijaya University have been studied. Therefore the objective of this study were to enhance quality of learning and learning outcomes at general biology course. The activity of lesson study was involved 41 students and 5 lecturers as observers. The method was used descriptive with using observation technique and literature study. Stages of lesson study are three such as plan, do, and see otherwise learning consisted of three cycles. First cycle describes respiration system, second cycle is blood circulation system, and third urogenital system. Model of learning of lesson study was Number Head Together (NHT). The research was concluded that lesson study could be enhanced quality of general biology and learning outcomes at general biology course.Keywords: lesson study, general biology, number head together